SPATIAL ANALYSIS OF STUNTING CASES IN OGAN KOMERING ULU (OKU), EAST OKU AND SOUTH OKU IN 2022 - Najmah Najmah; Salwa Syamsia; Melika Susilawati; Rizquita Azizah; Mita Julianti; Rini Oktarina; Citrasari; Dedy Irawan (LLDIKTI Wilayah X, 2025)
The incidence of stunting is still the focus of joint handling in Indonesia, including in Ogan Komering Ulu (OKU), East OKU and South OKU Districts because stunting has a long-scale negative impact. This study aims to analyze the prevalence of stunting, risk factors and stunting interventions in OKU, East OKU and South OKU districts in 2022 descriptively and spatially. The research method used is a quantitative approach using a case series study design or a series of stunting cases in OKU, East OKU and South OKU Districts which presents all cases of stunting detected by the South Sumatra Provincial Health Office in 2023. The highest stunting cases in OKU Regency are located in the Mendingin health center working area, which is 42 cases of stunting marked in solid red. This was followed by the Kedaton, Penyadingin, Tanjung Lengkayap and Pengandonan health center working areas. In East OKU District, all working areas health center have a low number of stunting cases. Whereas in South OKU District the the highest stunting cases are located in the working areas of the Sindang Danau and Buana Pemaca health center, which are marked in solid red marked with a solid red color. Exclusive breastfeeding proportions of 100% were detected in two health center OKU. Exclusive breastfeeding was almost 100% in two health center in East OKU and South OKU. Proportion of Complementary foods 100% was detected in four OKU and health center South OKU and two health center East OKU. The proportion of HB checks for pregnant women was 100% in seventeen health center in OKU, two in East OKU and one South OKU. Proportion of Fe tablets given to pregnant women 100% detected in two OKU health centers, four East OKU and three South OKU health centers.